Peran Teknologi Informasi dalam Penguatan Akuntabilitas dan Transparansi Lembaga Pengelola Wakaf - Nurhudawi; Ismail; Arifa Pratami; Tony Hidayat; Salman Nasution (Institute Agama Islam Tafaqquh Fiddin Dumai, 2026)
Waqf is an instrument in Islamic finance which functions as a means of realizing the benefit of society. Waqf practices require improvements in various aspects of management so that all the muwafiks' hopes can be realized. One effort to achieve good waqf management is by having good management accountability practices. The development of information technology has brought about a significant transformation in the governance of non-profit organizations, including waqf management institutions. In the midst of increasing public demands for accountability and transparency, the use of digital systems has become a strategic necessity to ensure waqf management is professional, credible and sustainable. This article aims to analyze the role of information technology in strengthening the accountability and transparency of waqf management institutions. This research uses qualitative methods through a literature study approach. The data obtained was then analyzed in stages, starting from the selection process, preparation, to drawing conclusions. Research findings show that information technology has a significant role in strengthening the accountability and transparency of waqf management institutions. The collection and distribution of waqf becomes more effective, efficient, transaction recording is more accurate by utilizing information technology, one of which is blockchain and digitalization of the waqf system. Increasing accountability and transparency will also increase community participation in waqf. Thus, information technology not only functions as an administrative tool, but also as a strategic instrument in building public trust in waqf management institutions. The integration of technology that is designed systematically and adaptively is an important prerequisite for realizing waqf management that is transparent, accountable and responsive to the dynamics of community needs. Keywords: Waqf, Information Technology, Blockchain, Digitalization, Accountability, Transparency